Pinocembrin Reduces Keratinocyte Activation and Ameliorates Imiquimod-Induced Psoriasis-like Dermatitis in BALB/c Mice through the Heme Oxygenase-1/Signal Transducer and Activator of Transcription 3 Pathway. (25th January 2022) - Huang, Kuo-Kuei; Lin, Meng-Nan; Hsu, Hui-Chun; Hsu, Yi-Ling; Huang, Ting-Ni; Lu, I-Huang; Pan, I-Hong
Abstract : Psoriasis is an autoimmune disease characterized by chronic skin inflammation and excessive keratinocyte proliferation. The itchy, scaly, and erythematous lesions present on psoriatic skin negatively affect patients' quality of life. Pinocembrin is a flavonoid present in propolis, fruits, and vegetables. It exerts neuroprotective effects and was used for treating ischemic stroke in a human clinical trial. However, the effects of pinocembrin on psoriasis have never been examined. In this study, we evaluated the effects of pinocembrin on human HaCaT keratinocytes and BALB/c mice with imiquimod- (IMQ-) induced psoriatic dermatitis. In interferon- γ - (IFN- γ -) activated HaCaT cells, pinocembrin reduced the expression of inflammatory cytokines, namely, tumor necrosis factor- α (TNF- α ), interleukin-6 (IL-6), and keratinocyte proliferation markers, namely, keratin (K)16, K17, and Ki-67. The mechanism underlying these inhibitory effects involved the regulation of the heme oxygenase- (HO-) 1/signal transducer and activator of transcription (STAT) 3 pathway. In the IMQ-induced psoriatic dermatitis mouse model, the topical application of pinocembrin significantly ameliorated the Skin Psoriasis Area and Severity Index score, epidermal thickness, inflammation, hyperplasia, hyperkeratosis, and cluster of differentiation (CD) 4 + T-cell infiltration. Expression of the inflammatory cytokines and keratinocyte proliferation markers in dorsal skin was significantly decreased in the pinocembrin-treated group. Meanwhile, in lesional skin, the expression of HO-1 was upregulated, but that of phospho-STAT3 (pSTAT3) was downregulated. Collectively, our results indicated the therapeutic potential of pinocembrin. Additional studies are warranted to evaluate its clinical benefits in patients with psoriasis.